Overcoming Counterproductive Work Behavior with Organizational Justice and a Job Satisfaction Approach - Reni Kurnia Permata; Pantius Drahen Soeling (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One of the detrimental behaviors that hinder organizational progress is Counterproductive Work Behavior. This behavior is continually being investigated in various organizations in the public and private sectors. This article describes the patterns, forms, and strengths found in different research results related to Counterproductive Work Behavior with the antecedents of Organizational Justice and Job Satisfaction. This article is a literature study. Based on the results of this literature study, Organizational Justice and Job Satisfaction are known to be related to Counterproductive Work Behavior in various patterns, forms, and strengths according to other factors that influence organizational conditions. The relationship’s pattern, form, and strength open the assumption of the mediating role of Job Satisfaction in the relationship between Organizational Justice and Counterproductive Work Behavior.